Selected areas in cryptography -- SAC 2016 : 23rd International Conference, St. John's, NL, Canada, August 10-12, 2016, Revised selected papers /: 23rd International Conference, St. John's, NL, Canada, August 10-12, 2016, Revised selected papers. (2017) - Unknown
No abstract available